2016
DOI: 10.1039/c5sm02220g
|View full text |Cite
|
Sign up to set email alerts
|

Migration of phospholipid vesicles in response to OHstimuli

Abstract: We demonstrate migration of phospholipid vesicles in response to a pH gradient. Upon simple micro-injection of a NaOH solution, the vesicles linearly moved to the tip of the micro-pipette and the migration velocity was proportional to the gradient of OH(-) concentration. Vesicle migration was characteristic of OH(-) ions and no migration was observed for monovalent salts or nonionic sucrose solutions. The migration of vesicles is quantitatively described by the surface tension gradient model where the hydrolys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 38 publications
2
34
0
Order By: Relevance
“…A line of our work has focused on studying the various effects of pH changes on giant unilamellar vesicle (GUV). We demonstrated that a pH change can induce vesicle migration and global deformation [5], as well as polarization in vesicles involving phase-separated membrane domains [6]. Furthermore, we showed that localized pH heterogeneities can induce local dynamical membrane deformations and developed a theoretical description of this phenomenon [7][8][9][10].…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…A line of our work has focused on studying the various effects of pH changes on giant unilamellar vesicle (GUV). We demonstrated that a pH change can induce vesicle migration and global deformation [5], as well as polarization in vesicles involving phase-separated membrane domains [6]. Furthermore, we showed that localized pH heterogeneities can induce local dynamical membrane deformations and developed a theoretical description of this phenomenon [7][8][9][10].…”
Section: Introductionmentioning
confidence: 87%
“…The flow, if existing, should occur inside the membrane and promote a visible vectorial motion of domains. Results on 2 types of vesicle migration phenomena were unable to detect such a motion on lipid vesicles which behaved as hard shells [5,66]. On the other hand, Marangoni effects have been found responsible for local deformations (see Section 4).…”
Section: Ph-induced Migrationmentioning
confidence: 98%
“…8 The position of the micro-pipette tip is (0,0,0). 8 The position of the micro-pipette tip is (0,0,0).…”
Section: Ph Field Generated By Micro-injectionmentioning
confidence: 99%
“…The excess membrane produced by the fusion clung to the fused spherical vesicle as a black patch at the contact zone (arrow in Fig. 8 Thus effects of the pH stimuli on vesicles depend on the types of amphiphilic molecules that compose the vesicle. Dissipative particle dynamics simulations propose the following dynamics of tension-induced vesicle fusion.…”
Section: View Article Onlinementioning
confidence: 99%
See 1 more Smart Citation